Evaluación del efecto de desinfectantes en la disminución de biopelícula en las redes de distribución de agua potable en el municipio El Rosal (2022)
The main objective of this project is to evaluate the effect of chlorine, chlorine dioxide and calcium hypochlorite in the reduction of biofilm in the drinking water treatment plant (PTAP) of the municipality of El Rosal and through experimental tests to select the most effective disinfectant. Initially, a compilation of the records of pH, color, turbidity and total iron of raw water and water at the outlet of the filtration stage was carried out, in addition to microbiological tests of total coliforms and Escherichia Coli, to establish the conditions of the treated water.